2002
DOI: 10.1046/j.1365-8711.2002.05069.x
|View full text |Cite
|
Sign up to set email alerts
|

The size and shape of local voids

Abstract: We study the size and shape of low‐density regions in the local Universe, which we identify in the smoothed density field of the PSCz flux‐limited IRAS galaxy catalogue. After quantifying the systematic biases that enter the detection of voids using our data set and method, we identify, using a smoothing length of 5 h−1 Mpc, 14 voids within 80 h−1 Mpc (having volumes 103 h−3 Mpc3) and, using a smoothing length of 10 h−1 Mpc, eight voids within 130 h−1 Mpc (having volumes 8×103 h−3 Mpc3). We study the void si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 43 publications
3
89
0
Order By: Relevance
“…Studies of the distribution of sizes of voids in the observed galaxy distribution have been performed (see, for example, Plionis & Basilakos 2002;Muller et al 2000;Muller & Maulbetsch 2004). An analysis of void properties with respect to CDM models and the effects of galaxy/dark matter biasing has been carried out by several authors (e.g., Mathis & White 2002;Benson et al 2003;Tikhonov & Klypin 2009;Tinker & Conroy 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the distribution of sizes of voids in the observed galaxy distribution have been performed (see, for example, Plionis & Basilakos 2002;Muller et al 2000;Muller & Maulbetsch 2004). An analysis of void properties with respect to CDM models and the effects of galaxy/dark matter biasing has been carried out by several authors (e.g., Mathis & White 2002;Benson et al 2003;Tikhonov & Klypin 2009;Tinker & Conroy 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Voids in the galaxy distribution account for about 95% of the total volume (see Kauffmann & Fairall, 1991;El-Ad, Piran & da Costa, 1996;El-Ad & Piran, 1997;Plionis & Basilakos, 2002;Rojas et al, 2005). The typical sizes of voids in the galaxy distribution depend on the galaxy population used to define the voids.…”
Section: Cosmic Depressions: the Voidsmentioning
confidence: 99%
“…Voids defined by galaxies brighter than a typical L * galaxy tend to have diameters of order 10 − 20h −1 Mpc, but voids associated with rare luminous galaxies can be considerably larger; diameters in the range of 20h −1 − 50h −1 Mpc are not uncommon (e.g. Plionis & Basilakos, 2002). These large sizes mean that only now we are beginning to probe a sufficiently large cosmological volume to allow meaningful statistics with voids to be done.…”
Section: Cosmic Depressions: the Voidsmentioning
confidence: 99%
See 2 more Smart Citations